Influence of Antistripping Additives and Rejuvenators on Healing Performance of Moisture-Damaged HMA - Dae-Wook Park; Tam Minh Phan; Yeong-Min Kim (Advances in Materials Science and Engineering)
This study aims to evaluate the effect of different rejuvenators and antistripping agents on the healing performance of hot mix asphalt (HMA). Two damage HMA series (e.g., moisture damage and aged damage) were subjected to either induction or microwave heating. A PG64-22 virgin and aged binder were used and modified with several additives. Three long-term aged binders (e.g., PAV5, PAV15, and PAV20) were conducted by pressure aging vessel (PAV) test. The moisture damage series fabricating with a new binder was further categorized into four different freeze-thaw (FT) cycles (e.g., 0FT, 1FT, 3FT, and 5FT). Also, the aged series was fabricated with three different aged binders. A total of eight damage-healing cycles were applied to all asphalt mixtures, examined by the three-point bending test. The moisture resistance of modified asphalt mixture was examined by indirect tensile strength test. Overall, asphalt mixtures modified with either antistripping additives or rejuvenators not only obtained higher moisture resistance but also gained better healing performance under moisture damage. In addition, the study showed a probable correlation between moisture damage and long-term aging in terms of healing performance, such as PAV15 and 3FT cycles and PAV20 and 5FT cycles.